A COMPARATIVE ANALYSIS OF FACTORS AFFECTING HOUSING AFFORDABILITY FOR LOW-INCOME GROUPS IN SUBURBAN AREAS OF JAKARTA, INDONESIA - Josephine, Esther; Wiranegara, Hanny W.; Supriatna, Yayat (International Journal on Livable Space, 2024)
The suburban areas of Jakarta have been chosen for the provision of subsidized housing to meet the needs of the Low-Income Community (MBR). The affordability level for MBR is a critical consideration in the provision of such housing. Suburban areas offer an advantage over inner-city areas due to relatively lower land prices. As a result, the development of housing for MBR has shifted to Jakarta's suburbs such as Bogor, Tangerang, and Bekasi Regencies. Previous research reviews have identified factors influencing MBR housing affordability, including housing location, housing accessibility, and travel behavior. Aims: This study aims to identify factors influencing Housing MBR affordability in Jakarta's suburban areas, including Tangerang, Bekasi, and Bogor Regencies. Methodology and results: Research variables include housing affordability, housing location, housing accessibility, and travel behavior. The research design uses a survey questionnaire method. The number of respondents from each regency is 40 MBR families residing in subsidized housing, randomly selected. The analysis technique used is multiple linear regression using Smart-PLS software. The study results show that the factors of housing location and travel behavior affect MBR housing affordability, while the accessibility factor does not. Conclusion, significance and impact study: In suburban areas, to make housing affordable for MBR, it is necessary to provide easily accessible, integrated, and affordable public transportation infrastructure; provision of various facilities accessible by walking/cycling; and considering the density of MBR housing to attract various parties to provide facilities.